Effect of platinum-lead nanoparticle as electrocatalyst for hydrogen generation over a wide pH range - Tan, Xuan Wen (Nanyang Technological University, 2022)
Water electrolysis has been a promising technology as an alternative of burning of fossil fuels to produce energy. However, the challenge to overcome the reactions' overpotential barrier has limited the use of this technology in large scale production.